2017
DOI: 10.1002/eco.1831
|View full text |Cite
|
Sign up to set email alerts
|

Microsite and grazing intensity drive infiltration in a semiarid woodland

Abstract: Human activities such as vegetation removal and overgrazing that result in changes in land cover have substantial impacts on ecosystem processes, including the infiltration of water. Different land cover types (microsites) vary in their capacity to conduct water, but the extent to which infiltration is affected by different herbivores or microsites is largely unknown. We examined the effects of grazing and microsite on infiltration in two extensive woodland communities in semiarid eastern Australia that vary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
4
20
0
Order By: Relevance
“…(c) Grazing increases both soil water and soil N in subsoil (Figure 4c), a finding consistent with some previous reports (Zhang et al., 2019; Zhou et al., 2017). Grazing leads to a more compact surface layer, the inevitable result of trampling, and that compact layer serves as a kind of insulation, preventing water from subsoil from rising to the surface (Vandandorj et al, 2017), and thereby conserving the water present in the deeper layers. Higher water content of the deeper layer, in turn, stimulates roots to go deeper (Hafner et al., 2012; Hamilton & Frank, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(c) Grazing increases both soil water and soil N in subsoil (Figure 4c), a finding consistent with some previous reports (Zhang et al., 2019; Zhou et al., 2017). Grazing leads to a more compact surface layer, the inevitable result of trampling, and that compact layer serves as a kind of insulation, preventing water from subsoil from rising to the surface (Vandandorj et al, 2017), and thereby conserving the water present in the deeper layers. Higher water content of the deeper layer, in turn, stimulates roots to go deeper (Hafner et al., 2012; Hamilton & Frank, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on Ethiopian highlands [34] revealed that proper management such as decreasing the grazing intensity or improving plant cover largely alleviates an adverse effect of grazing in steep than flat lands. Prescribed early fire tended to decrease water infiltration [25] and larger size animals can decrease the water infiltration rate more than smaller size animals such as rabbits and kangaroos [12]. Despite this complexity, the majority of earlier studies have demonstrated that heavy grazing has a detrimental impact on soil water infiltration while light and moderate grazing can be beneficial.…”
Section: Grazing Intensity and Frequencymentioning
confidence: 99%
“…The response of hydrologic processes to grazing methods is influenced by other factors such as management duration [29], topography [34], fire [25], and animal types [12], which are important to consider when determining the grazing intensity and frequency for a specific farm for better water management. For instance, a study on Arizona grasslands observed that grazing exclusion for 54 years had a greater infiltration rate than no-grazing for 25 or 10 years [29].…”
Section: Grazing Intensity and Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…In intensively grazed ecosystems, there are negative effects on soil properties because of the high livestock density. In such conditions, grazing increases soil compaction, eliminates cover protection and reduces key soil properties such as pH, electrical conductivity (Zhang et al, 2017), organic carbon, nitrogen (Byrnes et al, 2017), root biomass (Wang et al, 2017) and hydraulic conductivity (Vandanorj et al, 2017). Also, the use of veterinary antibiotics in cattle increases the content of these elements in the soil via animal droppings (Tasho and Cho, 2017).…”
mentioning
confidence: 99%